Coopetition and coordinated investment: protecting Japanese video games' intellectual property rights. (1st January 2014) - Ohkita, Kenichi; Okura, Mahito
This paper analyses coopetitive strategies pursued by game software firms faced with the problem of intellectual property rights violation. The most important finding is that although software firms have an incentive to invest in protecting their intellectual property rights, the amount invested without coopetition is lower than optimal. In other words, the situation where software firms cooperate by choosing the amount they invest but compete with quantities is desirable, but this cannot be realised if software firms have the option to voluntarily choose the amount they invest. On this basis, associations which game software firms join in exchange for a membership fee are useful as a mechanism to set an industry standard for investment and to cooperatively make efforts against illegal game software distributors.